(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In the Modern communication field, transmitting data through compact antennas like Microstrip patch antennas plays a major role. For Mobile radiolocation, satellite services, medical applications at Terahertz frequency range. Designing antennas for such applications at this frequency must have less weight and good characteristics. For this, graphene is the best suitable material for design due to its electrical, optical, and thermal conductivity properties. So, The Graphene-Based drilled substrate patch antenna 500 X 500 X 40 µm presents the simulation in the terahertz frequency. The prosed antenna structure is well suitable in the ISM (Industrial Scientific and Medical) band 1.36 THz-1.64THz 2.4 2.5 GHz. Its gives a high gain -20dB. Their Properties have been analyzed with CST for full-wave Simulations.